Child mortality and infant mortality in Catalonia (1700-1860) - Ferrer-Alós, Llorenç (2023)
There are very few studies on infant mortality in Catalonia. That is why is intended to study infant mortality (deaths under 12 years of age) and infant mortality (under 1 year of age) based on a systematic collection of mortality data from 243 parish series of baptisms and deaths in Catalonia between 1700 and 1860. The study is quantitative and territorialised to explore differential mortality. The result is that this type of mortality was particularly high in the second half of the 18th century and began to decline in the first half of the 19th century. It is also concluded that it was less intense in the smaller towns and that the reduction was more pronounced in the coastal towns. Finally, an approach is made to the evolution of infant mortality (0 to 1 years) in Catalonia, which corroborates the data on infant mortality.